Biodiversity of the Colorado State University lands - Smith, J. P., author; Balunek, E., author; Baldvins, T., author; Schuhmann, A., author; Anderson, D., author; Eastberg, O., author; Enebo, E., author; Garcia, K., author; Kim, M., author; Lansidel, D., author; Martinus, J., author; McCarty, C., author; et al. (Colorado State University. Libraries, 2022)
During the academic year of 2021-2022, the Colorado Natural Heritage Program (CNHP) was contracted by CSU Facilities Management to complete a biodiversity survey of the CSU lands. This assessment will be used by Facilities Management to self-report on the Biodiversity component of the Operations category in the STARS (Sustainability, Tracking, Assessment, & Ratings System) report. This report assesses endangered and vulnerable species (including migratory species) on CSU-owned and managed lands and areas of biodiversity importance on CSU-owned and managed lands. An additional aim of this project was to include students in the geospatial analysis, research, and field data collection efforts, thereby lowering project costs and providing mentorship and experience to the students. Biodiversity was assessed through a geospatial environmental review of the properties which includes documented and potential occurrences of regulatory species and other species of concern within the property and a 1-mile buffer, assessment of the conservation areas adjacent to the property and within a buffer, and the diversity and acreage of wetlands and other ecosystem types. The conservation value of each property, based on a Return-on-Investment report, is presented. Geospatial data area used to evaluate climate resiliency and landscape disturbance. Further research into species on the largest and most well-studied properties is presented, along with results of field work. Colorado State University holds 32 individual properties, spanning 14 counties across Colorado, covering a total of 3,943 hectares. Properties held by CSU had 303 documented occurrences of regulatory species and other species of concern within 1 mile returned in the environmental review; additionally, potential habitat was returned for another 2210 regulatory and other species of concern from a combination of range maps, general precision CNHP element occurrence records, and models. Through the many metrics of biodiversity assessed, several properties stood out; these included the Eastern Colorado Research Center, the Mountain Campus, Foothills, Horsetooth, and the Environmental Learning Center. At the Eastern Colorado Research Center, a combination of research field work recorded 187 species as visual observations and/or within a modeled area. At the Mountain Campus, student research and field work recorded a total of 1,044 species as visual observations and/or within a modeled area, with 754 Animalia species, 273 Plantae species and 17 Fungi species. Along with providing information on the biodiversity on the CSU lands, this project provided educational value to CSU students and facilitated the creation of a storymap to showcase the biodiversity of CSU lands to the public and stakeholders. The biodiversity assessment suggests several actions which could be taken to protect, enhance, or restore the biodiversity found on CSU lands and identified properties with possible conservation gains through enhancement and restoration.
Prepared for: Colorado State University Facilities Management.
June 2022.
Keywords: Colorado State University; Biodiversity -- Colorado